Comparative study between intravenous ramosetron and dexamethasone as pre-treatment to attenuate pain during intravenous propofol injection - Nayek, Sushil Kumar; Biswas, Chaitali (Eastern Journal of Medical Sciences, 2019)
Background: Propofol as an induction agent has disadvantage of pain on intravenous injection (IV). Objective: The aim of this study was to compare the efficacy of ramosetron and dexamethasone as a pretreatment drug for attenuation of pain due to propofol injection. Methods: This randomized comparative study was conducted at a tertiary care hospital in Eastern India, over a period of one year (March 2016-February 2017). Total 90 American Society of Anesthesiologists (ASA) grade I and II patients were randomly assigned into three groups (30 in each). Group R received 2 ml (0.3mg) of ramosetron, Group D received 2 ml (0.1mg/kg) of dexamethasone, and Group N received 2 ml of 0.9% normal saline. Venous drainage was occluded by using a tourniquet in mid-forearm before injecting the pre-treatment solution and released after 1 min and then 2 ml of propofol was injected over 5 sec. Patients were observed and questioned 15 sec later, if they had pain in the arm or discomfort during drug injection. The pain was scored on a four-point scale: 0 = no pain, 1 = mild pain, 2 = moderate pain, and 3 = severe pain. Pearson’s Chi Square test/Fisher’s Exact Test and Mann-Whitney U test/Kruskal Wallis Test were used to analyze the results. Results: The overall incidence of pain was 90% in the saline group, 17% in the ramosetron group and 10% in the dexamethasone group. The intensity of pain was significantly less in patients receiving ramosetron and dexamethasone than those receiving saline (P < 0.05). Haemodynamic parameters like heart rate (HR) and mean blood pressure (MBP) were recorded at different points of time. No significant inter group differences in MBP and HR were noted at any point of time. Conclusion: Pre-treatment with intravenous ramosetron and dexamethasone both lead to relief of pain on injection of IV propofol without any significant difference between their effects.